Civic And Values Education: The Role Of The Ncce In Promoting Honesty And Communalism In The Akatsi South Municipality Of Ghana - Adzika Vincent (University of Cape Coast, 2024)
The research looked at how the NCCE could incorporate values education as an additional component of its civic education mandate under the 1992 Constitution, explore the relationship between civic and values education, and promote the democratic values of honesty and communalism in Akatsi South Municipality. Fifteen participants within the Municipality were interviewed using a purposive sampling procedure, and interview questions were semi-structured. A qualitative research method was adopted, with the preferred research design being the case study. Data were analysed using thematic analysis, and the republican civic education theory served as a guide. Data was gathered in an audio format, transcribed, and thematically analysed to bring out the issues. The study uncovered that most of the residents of Akatsi South understand the concept of values in terms of morality and bring meaning into their lives, as opposed to values in terms of economic worth. It was likewise found that, despite a dainty line between civic and values education, the NCCE, a constitutionally established institution, is doing minimal in the space of values education. The findings further revealed that the NCCE could add values education as a derivative of its mandate because it fits its current approach to civic education and can be adopted as part of its fifth function provided for by Article 233(e) of the 1992 Constitution of the Republic of Ghana. It was also discovered that the citizens of Akatsi South know the democratic values of honesty and communalism, but the application of these two values continues to dwindle in both lives in public offices and among individuals in private life as compared to the near past. Laxity in applying the laws against wrongdoings and political equalisation among politically exposed persons and the open display of dishonesty with impunity has dramatically contributed to the low level of honesty and communal spirit among citizens.
Civic And Values Education: The Role Of The Ncce In Promoting Honesty And Communalism In The Akatsi South Municipality Of Ghana
xi,188p:,ill